Design and Optimization of Wireless Sensors for Smart Grid Applications in Energy Management - Ramya, D.; Kashyap, K.Abhinay; Kumar, K.Sanath; Manimekala, P.; Geena, M.G. (Journal of Neonatal Surgery, 2025)
This paper presents a comprehensive approach to smart energy management using IoT-based smart meters. The system provides real-time monitoring, predictive maintenance, and blockchain-secured communication for improved energy ef- ficiency. Results show substantial reductions in energy consump- tion and enhanced grid reliability. We analyze various wireless protocols,proposeanoptimizedsensornetwork,andvalidatethe approach with real-world case studies and simulations.